BUMI: ANTARA BULAT DAN DATAR? - Darlis . (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2023)
The debate over the shape of the Earth, whether flat or spherical, is not only a scientific issue but also a matter of interpretation. The conclusions of proponents of a flat Earth and a spherical Earth both stem from the same interpretation of verses. This research is a literature review based on interpretations and articles related to the issue. The approach used is a comparative study and uses semantic analysis of verses in the Qur'an that convey the meaning of "expansion." This article concludes that interpreters who assert a flat Earth are based on Qur'anic narratives that textually indicate the meaning of "expansion." Meanwhile, those who assert the Earth's shape is spherical understand the verses more as functional. The verses that describe the Earth's expansive condition do not explain the nature of its shape, but rather the Earth's function as a spacious and pleasant habitat for humans. This understanding is concluded from an analysis of the language of the Qur'an, which uses the word ja'ala, which emphasizes function, rather than the word khalqa, which indicates the form of creation.